Perception of Men in the Teaching Profession by Teaching Students - Anna Małgorzata Dudak (Maria Curie-Skłodowska University, Lublin, Poland, 2022)
Introduction: The study into the attitudes towards stereotypes in feminized professions has been inspired by the changing social roles, including professional roles, challenges to the stereotypical division into male and female roles, as well as the growing number of men who choose feminized professions. Research Aim: The aim of the research was to diagnose the emotional-appraisal component of the attitudes of teacher students towards men working in a feminised profession, using the teaching profession as an example. Method: The study used a diagnostic survey method, using semantic differential (Osgood et al., 1957) to investigate the attitudes of undergraduate teaching students towards men in a feminised profession using the teaching profession as an example. Results: The research revealed that students have relatively positive emotional attitudes towards men taking up work in feminised professions on the example of the teaching profession, especially towards the issue of men pursuing this profession because of their interests and the possibility of realising their aspirations. Respondents were the least positive about men in feminised professions towards the fact that they pursue this profession for lack of other opportunities and their awkwardness in life, but it is worth noting that these attitudes were at an average level. Conclusions: In the attitudes of the respondents, one can see a positive attitude towards the changes taking place in the perception of taking up roles and tasks defined by gender stereotypes. Gender and stereotypical assessment of predispositions to perform a specific job should not constitute a significant barrier to pursuing one's own career intentions.